2018
DOI: 10.1038/s41390-018-0137-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of antioxidant enzymes, total sialic acid, lipid bound sialic acid, vitamins and selected amino acids in children with phenylketonuria

Abstract: It was concluded that the levels of α-aminoadipic acid and phylloquinone might be an appropriate choice for the determination of phenylketonuria in parallel with the levels of phenylalanine. α-aminobutyric acid and phylloquinone as a supplement can decrease HPA damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 31 publications
0
15
1
2
Order By: Relevance
“…In a recent study by Suat Ekin on PKU patients, with a mean age of 6.92 ± 0.61 years (n = 30), a tendency of low levels of serum Ala, Gly, and Orn was exposed in patients, although no statistical difference was observed between the PAH deficiency group and healthy group . In our study, the older HPA children showed significantly lower levels of Tyr, Ala, Gly, Orn, Thr, Asp, Glu, Met, Arg, and Gln than in the corresponding control group, all with statistical difference.…”
Section: Discussioncontrasting
confidence: 61%
“…In a recent study by Suat Ekin on PKU patients, with a mean age of 6.92 ± 0.61 years (n = 30), a tendency of low levels of serum Ala, Gly, and Orn was exposed in patients, although no statistical difference was observed between the PAH deficiency group and healthy group . In our study, the older HPA children showed significantly lower levels of Tyr, Ala, Gly, Orn, Thr, Asp, Glu, Met, Arg, and Gln than in the corresponding control group, all with statistical difference.…”
Section: Discussioncontrasting
confidence: 61%
“…No entanto, alguns pesquisadores obtiveram resultados de médias semelhantes entre grupos caso e controle. Nos resultados de Artuch et al 9 , Gassió et al 24 e Ekin et al 7 , a diferença das médias entre caso e controle não demonstraram relevância, divergindo com o estudo de Bakel et al 8 , onde a redução foi de aproximadamente 50% e Reilly et al 18 , com diminuição de 37% em fenilcetonúricos (Figura 4).…”
Section: Demonstraram Resultados Semelhantes (Figura 2)unclassified
“…Estudos demonstraram deficiência na capacidade antioxidante, relacionando com a carência nutricional3,4, no entanto, divergências de resultados ocorreram referentes aos perfis de CoQ106, selênio 7,8 e glutationa peroxidase (GPx) 8,9 , surgindo a necessidade de responder através de um levantamento bibliográfico, se a carência nutricional realmente interfere de modo a comprometer a capacidade antioxidante.…”
Section: Introductionunclassified
“…Ekin et al [ 24 ] documented lower phylloquinone concentrations in their 30 PKU patients compared to 30 healthy peers. However, the authors did not assess the dietary and formula intake of vitamin K. It is also important to underline that their assessment comprised the measurement of vitamin K1 exclusively.…”
Section: Discussionmentioning
confidence: 99%